Development as Freedom in a Digital Age : Experiences from the Rural Poor in Bolivia - Gigler, Björn Sören (Washington, DC: World Bank, 2015)
Under what conditions can new technologies enhance the well-being of poor communities? The study designs an alternative evaluation framework (AEF) that applies Amartya Sen’s capability approach to the study of information and communications technologies (ICTs) in order to place people’s well-being, rather than technology, at the center of the study. The AEF develops an impact chain that examines the mechanisms by which access to, and meaningful use of, ICTs can enhance people’s “informational capabilities” and improve people’s human and social capabilities. This approach thus uses people’s individual and collective capabilities, rather than measures of access or use, as its principal evaluative space.